Diseño y construcción de un tablero didáctico para el laboratorío de maquinarias enfocado a la enseñanza de practicas con motores, específicamente para el control del proceso de sincronización de generadores y utilizando la herramienta de labview para la visualización - Gallegos, Diana (2009)
At present the college with the desire for students to relate to situations that arise in industry. Today, projects are undertaken in their area of specialty so it is essential to build a test panel with DC motors and AC. Here is the creation of an educational panel which consists of measurements of elements, strength and control, protection, performance indicators, terminal connection and so on. It also sees the need to create a monitoring system using LabVIEW software. The scope of this project is from study of elements for a variety of laboratory practices in the electrical machinery until you get to have all the tools to make the practice of sinchronization generators in parallel with this operation can be viewed through tool LabVIEW. Then testing and analysis results were satisfactory.